THE EFFECT OF CHILI PRICE IN INDONESIA ON MARKET DEMAND IN THE MONTH OF RAMADHAN - Utami, Ovi Fadilla; Dinda Amelia Putri; Grasella br Sinaga; Karina Susmita; Putri Maulidina Fadhilla; Tiur Malasari Siregar (JURNAL KREASI RAKYAT, 2023)
Usually on major holidays including the month of Ramadan, the price of chilies increases. However, in the month of Ramadan 2023, chili prices have decreased. The highest peak in the last month was IDR 46,774 on the first day of Ramadhan and after that it decreased, and the lowest price reached IDR 37,609. Meanwhile, cayenne pepper decreased from IDR 56,491 to IDR 42,353. This study aims to analyze the effect of chili prices on market demand in the month of Ramadan and look at the demand curve from the data. This type of research is descriptive research with a qualitative approach. Data collection in this study was by using secondary time series data originating from the Ministry of Agriculture and Trade, the Ministry of Agriculture, and the Central Bureau of Statistics (BPS). Data processing in research is by using the average formula and presentation to see the market demand curve. From this study, it can also be concluded that the average red chili and cayenne pepper have decreased since the beginning of this month of Ramadan.